“But Very Sluggish and Very Awkward”: Unconventional Ways of Representing Disability in Cultural Texts, from Poetry to Twenty-First-Century Cabaret Performances - Połetek, Mikołaj (Representations of Disability in Cultural Spaces, 2026)
The aim of this article was to analyze unconventional methods used by authors of various cultural texts to portray characters with disabilities. The study drew on works on a variety of topics (poetry, prose, film, cabaret performances) in which people with disabilities were prominent characters. The authors exploited the issue of disability in a rather inappropriate way to depict, among other things, the depth of suffering and to debunk negative stereotypes about people with disabilities, in order to highlight the fact that people perceived as “Others” are no different from able-bodied individuals. Disability often serves as a backdrop, with the prevailing harmful social conditions taking center stage. Unconventional creative techniques often include irony, comedy, and emotional or even pejorative vocabulary, which in the 21st century has acquired vulgar and stigmatizing meanings.